Research Progress of Doped Manganite Materials in Magnetic Refrigeration - Xie, Zhuojia; Zou, Zhengguang; He, Bangrong; Liu, Lilin; Mao, Zheng (Frontiers in Materials, 2021)
Magnetic refrigeration technology is a new, green, high-efficiency approach. It has attracted increasing attention from researchers and has a strong competitiveness over traditional refrigeration methods. With the continuous development of social lives, magnetic refrigeration technology must have important application prospects. This article briefly describes the basic principles. The focus is on the introduction and summary of research on perovskite manganite doping in magnetic refrigeration. Finally, the outlook and summary of magnetic refrigeration technology are presented.